Cangrelor in cardiogenic shock and after cardiopulmonary resuscitation: A global, multicenter, matched pair analysis with oral P2Y12 inhibition from the IABP-SHOCK II trial. (April 2019) - Droppa, Michal; Vaduganathan, Muthiah; Venkateswaran, Ramkumar V.; Singh, Abhayjit; Szumita, Paul M.; Roberts, Russel J.; Qamar, Arman; Hack, Luis; Rath, Dominik; Gawaz, Meinrad; Fuernau, Georg; de Waha-Thiele, Suzanne; et al.
Abstract: Aims: Cangrelor has a potentially favorable pharmacodynamic profile in cardiogenic shock (CS). We aimed to evaluate the clinical course of CS patients undergoing percutaneous coronary intervention (PCI) treated with cangrelor. Methods and results: We retrospectively identified 136 CS patients treated with cangrelor. Patients were 1:1 matched to CS patients from the IABP-SHOCK II trial not receiving cangrelor by age, sex, cardiac arrest, type of myocardial infarction, culprit lesion, glycoprotein IIb/IIIa inhibitor, and oral P2Y12 -receptor inhibitor and followed-up for 12 months. The study cohort consisted of 88 matched pairs. Thirty-day and 12-month mortality was 29.5% and 34.1% in cangrelor-treated patients and 36.4% and 47.1% in control group (P = 0.34 and P = 0.08, respectively). The rate of definite acute stent thrombosis was 2.3% in both groups. Moderate and severe bleeding events occurred in 21.6% in the cangrelor and 19.3% in the control group (P = 0.71). Patients treated with cangrelor more frequently experienced ≥1 TIMI flow grade improvement during PCI (92.9% vs. 81.2%, P = 0.02). Conclusion: Cangrelor treatment was associated with similar bleeding risk and significantly better TIMI flow improvement compared with oral P2Y12 inhibitors in CS patients undergoing PCI. The use of cangrelor in CS offers a potentially safe and effective antiplatelet option and should be evaluated in randomized trials.